Three Years After Soybean-Cover-Crop Rotation in Conventional and No-Till Practices: What Are the Consequences on Soil Nitrous Oxide Emissions? - Nokwanda O. Dlamini; Lindsay Banda; Laura M. Cardenas; Aranzazu Louro-Lopez; Jerry C. Dlamini (Nitrogen, 2025)
Nitrous oxide is a potent greenhouse gas due to its long atmospheric lifespan (121 years) that results in a high global warming potential (GWP). Research has shown that no-tillage may be implemented as a mitigation strategy to reduce N2O emissions. The objective of the was to evaluate how conventional tillage (CT) and no-tillage (NT) can potential influence N2O emissions in soybean rotation in a semi-arid region of the central Free State of South Africa. The effect of conventional and no-till tillage practices on N2O emissions under soybean rotation was evaluated in the 3rd year of a 5-year rotation system, in a semi-arid region of the Free State of South Africa, from December 2022 to December 2023. The experimental area was divided into three blocks and there were two plots in each block: in total there were six plots. The treatments were planted in a soybean rotation system under no-tillage and conventional tillage. The monthly averages of N2O emissions were significantly different from each other during the soybean growing season; the highest emissions were recorded in August/September 2023 from both the NT and CT treatments after harvest. During this time, there were crop residues in the soil that increased soil carbon. There was a positive correlation between N2O emissions and soil carbon content (p = 0.21) and between N2O emissions and soil organic matter (p = 0.43). Emissions were significantly higher in CT (LSD = 0.3) than in NT. The lowest N2O emissions were recorded in December 2023 (LSD = 0.05) and were significantly reduced in the no-till plots compared to those of the conventional tillage plots. Furthermore, the lowest cumulative N2O emissions of 0.26 ± 0.22 kg N2O-N ha−1 were recorded during NT in the winter season and were significantly different from CT (LSD = 0.19). The results from our study indicate that the no-till practices in soybean rotation can decrease N2O emissions.